THE NEXUS BETWEEN TRADE OPENNESS AND ENVIRONMENTAL DEGRADATION : A VECM ANALYSIS - Wicaksana, Tania; Widodo, Wahyu (LPPM Universitas Jambi, 2024)
This research aimed to analyze the influence of trade openness, ICT, per capita income, and Human Development Index on environmental quality in Upper-Middle Income countries in the short and long term and how per capita income influenced environmental quality in the U-shaped EKC hypothesis in Upper-Middle Income countries over the 1990-2020 periods using the VECM Panel analysis. Several findings were revealed in this research. First, the coefficient of trade openness in the long-term and short-term on environmental quality was positive and statistically significant at the 1% level. Second, the relationship between ICT and environmental quality had a positive influence in the short term and a negative influence in the long term. Third, the relationship between per capita income and environmental quality positively influenced the long- and short-term. In these findings, an increase in per capita income increased carbon dioxide, which caused a decrease in environmental quality and emerged an inverted U relationship in the long- and short-term of the EKC hypothesis in UMI countries, with the turning point in the short-term being US 728,530 and in the long-term US 772,839. Finally, the Human Development Index in this research positively influences environmental quality in the short- and long-term. The outcomes of this study have considerable Policy implications regarding trade openness policy formulation to reduce environmental degradation, especially in Upper Middle-Income Countries.